Kontinuitas Teologi Klasik dalam Dunia Islam - Wahyuddin G (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2011)
Classical theology of Islam spread broadly to Islamic community in wider context. The concept of faith, believer, unbeliever, heaven and hell as the main themes of classical theology have undergone the changes of substantial meaning. The current theology not only discuss the above theme as, but also focuse on how to harmonize the relation between religions. There has been the sustainity and continuation of theological school form Jabariyah to a moderate one such Asy’ariah, whereas, Qadariyah-Mu’tazilah’s theology has metamorphosed into liberal-inclusve theology.